Interaction between the GROWTH-REGULATING FACTOR and KNOTTED1-LIKE HOMEOBOX Families of Transcription Factors . Issue 4 (14th February 2014) - Kuijt, Suzanne J.H.; Greco, Raffaella; Agalou, Adamantia; Shao, Jingxia; 't Hoen, Corine C.J.; Övernäs, Elin; Osnato, Michela; Curiale, Serena; Meynard, Donaldo; van Gulik, Robert; Maraschin, Simone de Faria; Atallah, Mirna; et al.
Abstract : Members of the GRF family are conserved transcriptional regulators in both monocot and dicot plants . Abstract: KNOTTED1-LIKE HOMEOBOX ( KNOX ) genes are important regulators of meristem function, and a complex network of transcription factors ensures tight control of their expression. Here, we show that members of the GROWTH-REGULATING FACTOR (GRF) family act as players in this network. A yeast ( Saccharomyces cerevisiae ) one-hybrid screen with the upstream sequence of the KNOX gene Oskn2 from rice ( Oryza sativa ) resulted in isolation of OsGRF3 and OsGRF10. Specific binding to a region in the untranslated leader sequence of Oskn2 was confirmed by yeast and in vitro binding assays. ProOskn2:β-glucuronidase reporter expression was down-regulated by OsGRF3 and OsGRF10 in vivo, suggesting that these proteins function as transcriptional repressors. Likewise, we found that the GRF protein BGRF1 from barley ( Hordeum vulgare ) could act as a repressor on an intron sequence in the KNOX gene Hooded / Barley Knotted3 ( Bkn3 ) and that AtGRF4, AtGRF5, and AtGRF6 from Arabidopsis ( Arabidopsis thaliana ) could repress KNOTTED-LIKE FROM ARABIDOPSIS THALIANA2 ( KNAT2 ) promoter activity. OsGRF overexpression phenotypes in rice were consistent with aberrant meristematic activity, showing reduced formation of tillers and internodes and extensive adventitious root/shoot formation on nodes. These effects were associated with down-regulation of endogenous Oskn2 expression by OsGRF3. Conversely, RNA interference silencing of OsGRF3, OsGRF4, and OsGRF5 resulted in dwarfism, delayed growth and inflorescence formation, and up-regulation of Oskn2 . These data demonstrate conserved interactions between the GRF and KNOX families of transcription factors in both monocot and dicot plants.